Adenylosuccinic acid: a novel inducer of the cytoprotectant Nrf2 with efficacy in Duchenne muscular dystrophy. (4th March 2021) - Rybalka, Emma; Goodman, Craig A.; Campelj, Dean G.; Hayes, Alan; Timpani, Cara A.
Abstract: Adenylosuccinic acid (ASA) modifies Duchenne muscular dystrophy (DMD) progression in dystrophic mdx mice and human DMD patients. Despite an established role for ASA in augmenting metabolism and cellular energy homeostasis, our previous data suggests an undiscovered ulterior mode of action capable of modifying DMD disease course. Here, we identify ASA as a novel inducer of nuclear factor erythroid 2-related factor-2 (Nrf2), master regulator of the antioxidant and cytoprotective response to cell stress.